STRATEGI PENGAMBILAN KEPUTUSAN DALAM PEMILIHAN MEDIA IKLAN MENGGUNAKAN FUZZY AHP - Komarudin, Rachman (Jurnal Pilar Nusa Mandiri, 2016)
Advertising is all Forms of presentation and promotion of ideas, goods, or services non-personal Certain Payments require a sponsor. Media Advertising is a tool to introduce the of products OR services marketed To Market, in addition to media advertising Many Ways to introduce of Company products, but ad Very Important role Marketing . The purpose of advertising is very dependent from company, good for the review to inform, persuade, OR warned. Research Strategy Decision Making In the Electoral Media Advertising Using Fuzzy AHP, expected MAY be used as a strategic alternative media choose the ads, research will study the problems Based on the criteria and sub-criteria Anything it takes formulate and Determine alternative development strategy Media Election ad, Research Model assessed According to a to Determine the scale of your priorities based on the weighted Priority Decision Making Media ad. From Preparation hierarchy Criteria Obtained 3 Criteria and 6 sub criteria and the four alternatives the which are used to review advertising media poll, based on the data processing Fuzzy AHP, Criteria for Internal factors, Vision, Mission and Target Market has the highest priority for review of choosing advertising media and newspaper Obtained Media Selected Notes Notes is based on the highest.